Influence of band microstructure on carbide precipitation behavior and toughness of 1 GPa-grade ultra-heavy gauge low-alloy steel - Han, Peng; Liu, Zhipeng; Xie, Zhenjia; Wang, Hua; Jin, Yaohui; Wang, Xuelin; Shang, Chengjia (International journal of minerals, metallurgy and materials, 2023)
This study investigated the influence of band microstructure induced by centerline segregation on carbide precipitation behavior and toughness in an 80 mm-thick 1 GPa low-carbon low-alloy steel plate. The quarter-thickness (1/4t) and half-thickness (1/2t) regions of the plate exhibited similar ductility and toughness after quenching. After tempering, the 1/4t region exhibited ∼50% and ∼25% enhancements in both the total elongation and low-temperature toughness at −40°C, respectively, without a decrease in yield strength, whereas the toughness of the 1/2t region decreased by ∼46°%. After quenching, both the 1/4t and 1/2t regions exhibited lower bainite and lath martensite concentrations, but only the 1/2t region exhibited microstructure bands. Moreover, the tempered 1/4t region featured uniformly dispersed short rod-like M 23 C 6 carbides, and spherical MC precipitates with diameters of ∼20–100 nm and <20 nm, respectively. The uniformly dispersed nanosized M 23 C 6 carbides and MC precipitates contributed to the balance of high strength and high toughness. The band microstructure of the tempered 1/2t region featured a high density of large needle-like M 3 C carbides. The length and width of the large M 3 C carbides were ∼200–500 nm and ∼20–50 nm, respectively. Fractography analysis revealed that the high density of large carbides led to delamination cleavage fracture, which significantly deteriorated toughness.